Influence of Additive, Age of Foliage and Application Technique on the Control of Imperata Cylindrica (L.) Beauv. With Dalapon and Glyphosate - Yeoh, Chong Hoe (1981)
Experiments were conducted to evaluate the influence of ammonium sulphate as an additive to dalapon (2, 2-dichloropropionic acid, Mg/Na salt) and glyphosate N (phosphonomethyl) glycinel and the influence of age of foliage and spray volume., on the control of lalang imperata cylindrica (L.) Beauty. The most effective site of uptake of glyphosate in the control of lalang was also determined. Higher rates of glyphosate (2.0 kg/ha) and dalapon (15 kg/ha) gave higher leaf injury ratings on the 1-,3- and 6-month foliage treatments compared to lower rates (1.5 and 10 kg/ha respectively) in both the field and pot experiments. Improved ciontrol with higher glyphosate rate was also reflected in the significantly lower dry weight of rhizomes harvested 90 days after treatment in the pot experiment. There were no significant differences in the two levels (10 and 15 kg/ha) of dalapon used in terms of weight of rhizomes irrespective of foliage age in both the experiments. At the usual recommended rates, glyphosate gave better control of lalang than dalapon in both the field and pottrials; glyphosate was also more effective on younger foliage than dalapon. The results also suggest that there was no advantage in cutting the lalang foliage and treating the young foliage regrowth with dalapon . Significant antagonistic responses due to ammonium sulphate (5 kg/ha) as additive were obtained with 1-and 3-month old foliage treatments at the 10 kg /ha dalapon level.